STUDI FENOMENOLOGI PADA PROSES ADAPTASI KOMUNIKASI GURU DALAM PEMBELAJARAN DIGITAL DI ERA PANDEMI - Tesya Sonia (2022)
This study aims to describe the teacher's experience while adapting communication in digital learning in the pandemic era. This study uses a qualitative approach with the phenomenological method, the reason the researcher chooses the phenomenological method is because this method can help researchers get in-depth information. To describe the experience of the teacher adaptation process at Elementary School X in West Jakarta more realistically and in detail, this study used data collection techniques with in-depth interviews conducted online using the zoom application to 6 informants of elementary school teachers X in West Jakarta. This study focuses on the communication experience of the communication adaptation process of SD X teachers in West Jakarta in the digital learning process in the era of the covid-19 pandemic. Data analysis techniques used in the research include, collection of life experiences, horizontalization, significant statements, thematic analysis, essence statements. The conclusion from the findings of research in the field is that, while adapting, the informants feel stress, shock and some feel happy and live it properly. The feelings felt by these informants were grounded because the digital learning transition was carried out without careful planning. This makes informants experience obstacles or obstacles in adapting digital learning, namely, difficulty using devices, weak internet connections so that they interfere with learning such as being, delaying and leaving the zoom room, fatigue and lack of focus in digital learning to character assessment. Keywords : Phenomenology, Covid-19 Pandemic, Distance Learning, Communication Experience.